Neuroprotective potential of Naringenin-loaded solid-lipid nanoparticles against rotenone-induced Parkinson’s disease model - Megala Mani, Shivaramakrishnan Balasubramanian, Kishore R. Manikandan, Balashanmugam Kulandaivel (Journal of Applied Pharmaceutical Science, 2021)
Currently available drug therapies are used to treat Parkinson’s disease (PD) by managing the clinical manifestations but not halt disease progression. Antioxidants as efficient organ-protective agents have been an integral part of human diet. Owing to the antioxidant’s chemical nature, crossing blood–brain barrier was a clinical challenge. Upon our initial screening of antioxidants by in silico and Drosophila studies, we identified Naringenin for studying its neuroprotective potential in rotenone (ROT)-induced PD rodent model. For better bioavailability in brain, Naringenin was loaded into solid-lipid nanoparticles (SLN) and evaluated. The results showed average particle size of 134.5 ± 20 nm, polydispersity index of 0.893, zeta potential of −11.9 mV, and entrapment efficiency of 89.87% ± 0.15%. In vitro release profile using dialysis technique follows the Higuchi model with the regression coefficient R2 of 0.9721. Neuroprotective activity of Naringenin–SLN was evaluated by ROT-induced PD rodent model. Results of behavioral observations and biomarkers provide an insight on the hypothesis that Naringenin as an SLN can exert neuroprotective effects, with the prospective to avert the progression of PD. Further studies are warranted in understanding the potential of antioxidants in the advanced delivery systems and to promote cost-effective large manufacturing of such formulations.
Keywords: Parkinson’s disease, oxidative stress, antioxidants, Naringenin, solid-lipid nanoparticles, rotenone.